(NuDOKAN (B:s (N|KONOMIKO(B-(NGEOGRAFI^ESKIE PROBLEMY OSWOENIQ (B: [(NsBORNIK STATEJ(B] /s - (NnEDE[EW(B, (NaLEKSEJ aLEKSANDROWI^s ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1987)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (N~ITIN(B. (NIN(B-(NT PRIROD(B. (NRESURSOWs
Keywords: (N|KONOMI^ESKAQ GEOGRAFIQs -- (N~ITINSKAQ OBLASTXs